Breast Cancer Screening in Sarawak, Borneo: 10 Years’ Community Outreach Program - Melissa Lim, Siaw Han; Shirley Tan, Siang Ning; Juriah, Sulehan; Zulkifli, Jantan; Sharifah Ashrina, Wan Ali; Nafeesa, Mat Ali; Mohamad Adam, Bujang; Yolanda, Augustin (John Wiley & Sons Australia, Ltd, 2025)
Abstract Background: Sarawak, largest state in Malaysia with 2.9 million population with 45% living more than 100km from urban cities. These communities face the risk of delayed breast cancer diagnosis due to limited access to healthcare services. Sarawak has only four government hospitals with diagnostic mammogram facilities. Objective: Sarawak Breast Cancer Support Group (SBCSG) has spearheaded breast cancer education and early screening outreach since 2012, with a special focus on rural communities. This paper describes the results from our 10-year program.